Transmembrane activator and CAML interactor (TACI) : another potential target for immunotherapy of multiple myeloma? - Xu, Shengli (2021)
Multiple myeloma (MM) has emerged as the next most likely oncological or hematological disease indication amenable for cellular immunotherapy. Much of the attention has been focused on B cell maturation antigen (BCMA) as a unique cell surface protein on myeloma cells that is available for monoclonal antibodies, antibody drug conjugates (ADCs), T-cell redirecting bispecific molecules, and chimeric antigen receptor (CAR) T cell targeting. BCMA is a member of the tumor necrosis factor receptor (TNFR) superfamily that binds two ligands B-cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) and mediates the growth and survival of plasma and MM cells. Interestingly, transmembrane activator and CAML interactor (TACI), another TNFR superfamily member, also binds the same ligands and plays largely overlapping roles as BCMA in normal plasma and malignant MM cells. In this article, we review the biology of TACI, focusing on its role in normal B and plasma cells and malignant MM cells, and also discuss various ways to incorporate TACI as a potential target for immunotherapies against MM.